The Effect of Classroom Management on Teacher Performance: Evident from Madrasah Ibtidaiyah in Indonesia - Suryani, Yani; Ilzamudin, Ilzamudin; Suryapermana, Nana; Sapi'i, Iing; Juhji, Juhji (Management of Education: Jurnal Manajemen Pendidikan Islam, 2025)
This study examined the effect of classroom management on teacher performance in a State Islamic Elementary School (Madrasah Ibtidaiyah Negeri) in Tangerang Regency, Indonesia. A quantitative survey design was used, involving 155 teachers selected through proportional random sampling from a population of 252 teachers. Data were collected using a validated questionnaire measuring classroom management and teacher performance, and analyzed using descriptive statistics and simple linear regression. The results indicated that classroom management had a positive and statistically significant effect on teacher performance (β = 0.366, t = 6.502, p < 0.001). The regression model explained 35.5% of the variance in teacher performance (R² = 0.355), indicating moderate explanatory power. These findings suggest that effective classroom organization, behavior management, and instructional structuring contribute substantially to teacher professional effectiveness. The study concludes that strengthening classroom management competencies is crucial for improving teacher performance in Islamic elementary schools. Practical implications highlight the importance of targeted professional development and instructional supervision focused on classroom-based practices.